Effect of congestion on the performance of IEEE 802.11 network. (24th March 2009) - Jain, A.K.; Sharma, S.C.; Jha, R.; Manoj, K.
Unlike the wired networks, congestion measurement in IEEE 802.11 networks is more difficult owing to factors such as time-variant channel capacity and contention among neighbouring nodes. It degrades the throughput and increases delay and packet drops. This paper presents an overview on IEEE 802.11 networks and issue of congestion in them. OPNET simulations were carried out to estimate the effect of congestion situation on the performance of the network model. Simulations were carried out at 11 Mbps data rate except congested node and total simulation time used was 900 simulations-seconds.